Judo and swimming training coaches opportunities in Brazil - Mazzei, L.; Siva Filho, F.; Böhme, M. T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
For a country to achieve international sporting success, beyond financial investment, is necessary to develop some strategic points in national sport structure. The training of coaches is a strategic factor that can optimize the international sport results. (GRENN & OAKLEY, 2001; DE BOSSCHER et al 2006). According Erickson et al (2008) formal education of coaches is one of the possible ways of purchase knowledge. The aim of this study was to identify the training coaches opportunities in swimming and judo in Brazil. Methods: A total of 18 elite sport coaches of São Paulo sport clubs (7 of judo and 11 of swimming) answered the following question: `What is the entity`s policy to training human resources for elite sport?" This paper is part of a research which is being conducted in São Paulo/Brazil. Data was obtained through personal interviews. Results: were analyzed through "Group Character Speech Method" (GCS), as proposed by Lefévre & Lefevre (2003). Results There was a similarity in some "Central Ideas" between judo and swimming, as the `The club itself promotes actions` was cited by 66,6% of coaches. However, other "CI" were specific to each modality, how "no exist" (33.3%) for the judo coaches and `is a coach responsibility` (16.6%) for swimming coaches. Discussion: The results show that some clubs promote training coaches through their own actions, for example, study groups, guest speakers and subsidies for participation in international events. Another important point in the survey is that judo coaches reported that `there is any one" policy or training coaches activities. In some countries with international success there are training programs for coaches in various forms, which are developed by a national sporting organization. Conclusion There is no proposed action related to the training of coaches in judo and swimming conducted by national bodies responsible for the organization of sport in Brazil. Clubs and coaches responsible for their own training